Effects of polyunsaturated fatty acid and diacylglycerol on the crystallization behaviors of palm-based oil - Ke, Wanting; Lee, Yee-Ying; Tan, Chin-Ping; Li, Aijun; Zhang, Yufei; Wang, Yong; Zhang, Zhen (Elsevier Ltd, 2025)
Diacylglycerol (DAG) is a novel functional structural lipid, but its application in base oils remains underexplored. This research investigated the effect of three liquid oils (groundnut oil, corn oil, and flaxseed oil), with varying polyunsaturated fatty acid (PUFA) (39.60, 69.50, and 77.65 %) and DAG content (0.00, 40.00, 80.00 %), on the crystallization behaviors of palm-based oil. DAG (40.00 %), obtained through enzymatic glycerolysis and molecular distillation, was found to stabilize the binary system with good compatibility and fine crystal structure. “Liquid” DAG played a dual role: diluting solid lipids, and promoting crystallization. Increasing DAG content led to larger crystalline domain size, while higher PUFA content accelerated crystallization and increased crystal orderliness, though decreasing crystal density. These results demonstrated the clear influence of PUFA and DAG content on palm-based oil crystallization. This knowledge can guide the utilization of different unsaturated DAGs for tailored fat crystallization in food application.